Kemitraan Pertanian: Melalui Asas Proporsionalitas Dengan Sistem Mudharabah - Firdausi, M. R.; Susanti, Dyah Ochtorina; Ali, Moh.; Fimaulidina, Noor Rizqiya (Widya Yuridika, 2024)
The decline in economic growth has an impact on increasing unemployment rates, both in the industrial and agricultural sectors, thereby making the poor population increase and becoming one of the groups most vulnerable to the impact of the Covid-19 pandemic. That is the fate of farmers who have been hit by the impact of the Covid-19 pandemic, and their situation is increasingly far from the prospect of achieving prosperity. Considering this, there is a need for a concept that can be an alternative for improving farmers’ welfare through agricultural partnership patterns. In this regard, updating the agricultural partnership agreement model based on the principle of proportionality, in combining the muzara’ah contract with the mudharabah system, could be an alternative. This research is a normative legal research that analyzes legal rules relating to the principle of proportionality, muzara’ah contracts with the mudharabah system. The focus of research in this journal is: First, understanding and describing muzara’ah contract collaboration with the mudharabah system in the rice farming partnership pattern. Second, understand and seek justice based on the principle of proportionality of the muzara’ah contract with the mudharabah system in the rice farming partnership pattern.